ENZIME ACTIVITY OF HIGHER BASIDIOMYCETES MUSHROOM SCHIZOPHYLLUM COMMUNE - Бухало, А.С.; Дуган, О.М.; Максимюк, М.Р.; Ліновицька, В.М. (Proceedings of National Aviation University (archive), 2012)
The purpose of this work was a revelation and evaluation of spectrum and activity of hydrolytic enzymes of higher basidiomycetes Schizophyllum commune in a surface and submerged culture. 21 strains of S. commune were object of investigation. Researches were conducted by standard microbiological, biochemical and biotechnological methods. All strains on agar mediums were shown the following enzymes: amylase, caseinase, gelatinase, polygalacturonase, pectattranselyminase, urease, lipase, cellulase, laccase and peroxydase. The demonstration of oxidizing enzymes of laccase and peroxydase depended on composition of medium. The estimation of presence and level of activity of endo-1,4-b-glucanase, exoglucanase and monophenolmonooxygenase at submerged cultivation indicate primary influence of components of complex nourishing medium on enzyme activity of strain 1760 S. commune.